Zhu Rongji on the Record : The Road to Reform: 1998-2003 - Zhu, Rongji, 1928- (Book collections on Project MUSE., 2015)
China's explosive transformation from a planned economy to a more market-oriented one over the past three decades owes much to the charismatic reformer Zhu Rongji. As China's premier from 1998 to 2003, Zhu displayed a pragmatism and strong work ethic that have been key forces in China's drive to greater modernization and global stature. During this time, Zhu embarked on a plan to reduce the size of government and reform the heavily indebted banking system and state-owned enterprises as well as to overhaul the housing and health care systems. His sweeping efforts ranged from lobbying for the establishment of stock exchanges to revitalizing agriculture through the introduction of a modern grain market. The ramifications of these reforms are still being felt throughout China and the globe, and The Road to Reform provides a real-time look at these plans as they were being formulated during the 1990s to the early 2000s. The second of a two-volume collection containing more than 100 speeches and personal papers by Zhu, this volume is a revealing and insightful look at Zhu's thinking and will lead to greater understanding of one of the world's two largest economic powers.